2009
DOI: 10.1007/s11064-008-9899-y
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of BACE1 and β-Amyloid Protein Mediated by Chronic Cerebral Hypoperfusion Contributes to Cognitive Impairment and Pathogenesis of Alzheimer’s Disease

Abstract: Chronic cerebral hypoperfusion (CCH) increases the risk of Alzheimer disease (AD) through several biologically plausible pathways, but the relationship between CCH and the development of AD remains uncertain. To investigate expression of APP, BACE1 and A beta in the hippocampus of BCCAO rats and study pathophysiological mechanism of AD from CCH. CCH rat model was established by chronic bilateral common carotid artery occlusion (BCCAO). Behavior was evaluated after BCCAO with Morris water maze and open-field ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 67 publications
2
59
0
Order By: Relevance
“…C99 is then further cleaved by γ-secretase within the hydrophobic transmembrane domain at either Val711 or Ile713, finally releasing Aβ and the intracellular domain of APP. The non-amyloidogenic pathway, in which APP is sequentially cleaved by α-and γ-secretase, may prevent the production of Aβ (116,117). Several studies have reported that propargylamine-containing compounds, including ladostigil and M30, irreversible and selective MAO-B inhibitors, act as modulators of the proteolytic cleavage of APP via activation of the p42/44MAPK and PKC signaling pathways (61,(118)(119)(120).…”
Section: Activated Mao Contributes To the Formation Of Amyloid Plaquesmentioning
confidence: 99%
“…C99 is then further cleaved by γ-secretase within the hydrophobic transmembrane domain at either Val711 or Ile713, finally releasing Aβ and the intracellular domain of APP. The non-amyloidogenic pathway, in which APP is sequentially cleaved by α-and γ-secretase, may prevent the production of Aβ (116,117). Several studies have reported that propargylamine-containing compounds, including ladostigil and M30, irreversible and selective MAO-B inhibitors, act as modulators of the proteolytic cleavage of APP via activation of the p42/44MAPK and PKC signaling pathways (61,(118)(119)(120).…”
Section: Activated Mao Contributes To the Formation Of Amyloid Plaquesmentioning
confidence: 99%
“…White matter damage is detectable with diffusion tensor imaging (DTI) at the early stages of brain injury following CCH (Wang et al, 2015). In addition, cerebral hypoperfusion accelerates cerebral amyloid angiopathy (Okamoto et al, 2012), enhances tau hyperphosphorylation, upregulates β-amyloid precursor protein cleavage enzyme 1 (BACE1) and β-amyloid level in the brain (Zhiyou et al, 2009), the main neuropathological hallmarks of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, hypoxia modulates the expression and activity of A␤-metabolizing enzymes, resulting in increased A␤ peptides, including the deleterious A␤(1-42) (Sun et al, 2006;Guglielmotto et al, 2009;Pluta et al, 2013). Moreover, an increased susceptibility to ischemia has been shown in the brains of amyloid precursor protein (APP)-overexpressing mice (Zhang et al, 1997). However, a causal relationship between AD and brain ischemia at the molecular and functional level has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, RAGE (Receptor for Advanced Glycation Endproducts) expression changes in neuronal and non-neuronal cells under ischemic conditions (Pichiule et al, 2007;Zhai et al, 2008) and AD (Yan et al, 1996). RAGE is a receptor mediating and focusing A␤ effects on neuronal and non-neuronal cells (Yan et al, 1995;Deane et al, 2003), contributing to A␤-dependent functional impairment in hippocampus and entorhinal cortex (EC; Origlia et al, 2008Origlia et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%